Pengaruh Hambatan Samping Terhadap Kinerja Ruas Jalan Kota Makassar (Studi Kasus : Ruas Jalan Bandang) - Hisky Valen Kala' (Universitas Kristen Indonesia Paulus, 2025)
Traffic congestion in big cities is often a major problem on urban roads, including in Makassar City. Jalan Bandang, which is the main access road, also experiences the same thing as the surrounding area which is dense with community activities such as shops, schools, offices, restaurants and places of worship. The purpose of this study is to determine the performance of urban road sections with shophouse land use. Data from direct field surveys collect information on traffic volume, lateral friction, vehicle speed and road geometry. Population data is also used as secondary data. The data was processed using the 2014 Indonesia Road Capacity Guidelines. Based on calculations and data analysis from three days of observation, the maximum traffic on the northern route on Monday was determined to be 1766.0 vehicles/hour. The highest traffic barrier was in the north on Wednesday with a vehicle density of 0.445.